Influence of concrete topping on behaviour of prestressed Hollow Core floor slabs on flexible supports - Wit Derkowski; Mateusz Surma (Budownictwo i Architektura, 2013)
Slim Floors (SF) are the structures made of the Hollow Core (HC) slabs supported on the slender beams, where the beam height is usually slightly greater than the height of precast slab element. With the increase of the supports' deflection, the deformation of the HC slab occurs, and in consequence, additional transverse normal and shear stresses appear in the precast element, which can cause a diagonal cracking and destruction of external webs of this element. It may also result in longitudinal cracks on bottom surface of the slab. Despite the frequent implementation of this type of structures, the existing standard EN 1168 gave only a brief record of the need to take the reduction in design shear capacity into account, but is not given any calculation procedure.